Clinical and Biological Validation of an Allogeneous Cancellous Bone Block for Alveolar Maxillary Ridge Reconstruction: A Case Series - Alexandre Perez; Elena Pierantozzi; Roberto Di Felice; Tommaso Lombardi (MDPI AG, 2024)
This exploratory case series clinically and histologically investigated the performance of allogeneic cancellous freeze-dried bone allograft (FDBA) bone blocks (Maxgraft®) for the lateral augmentation of local alveolar defects in the posterior maxilla as part of two-staged implant therapy. Five patients receiving eight implants 5 months after block augmentation with a follow-up period of up to 3 years were documented and analyzed. Horizontal alveolar dimensions before and 5 months after block augmentation were quantified using CBCT. Radiographic marginal bone level changes were quantified at implant placement, loading, and 1 year post-placement. Graft integration and resorption were histologically qualitatively evaluated from core biopsies retrieved at implant placement. Block augmentations resulted in a pronounced horizontal median bone gain of 7.0 (5.5 to 7.8) mm. Marginal implant bone levels in block-augmented bone remained constant over the 1 year follow-up period. Block grafts appeared histologically well integrated. Histologic analysis also revealed signs of progressive resorption and new bone formation at the lateral aspects of the grafts. The results of this case series support using Maxgraft® cancellous FDBA blocks as suitable materials for the lateral augmentation of local alveolar defects.